Fire exit : a novel - Talty, Morgan, 1991- (Tin House, 2024)
"From the porch of his home, Charles Lamosway has watched the life he might have had unfold across the river on Maine's Penobscot Reservation. On the far bank, he caught brief moments of his neighbor Elizabeth's life--from the day she came home from the hospital to her early twenties. But there's always been something deeper and more dangerous than the river that divides him from her and the rest of the tribal community. It's the secret that Elizabeth is his daughter, a secret Charles is no longer willing to keep. Now, it's been weeks since he's seen Elizabeth, and Charles is worried. As he attempts to hold on to and care for what he can--his home and property; his alcoholic, quick-tempered, and bighearted friend Bobby; and his mother, Louise, who is slipping ever deeper into dementia--he becomes increasingly haunted by his past. Forced to confront a lost childhood on the reservation, a love affair cut short, and the death of his beloved stepfather, Fredrick, in a hunting accident--a death he and Louise are at odds over as to where to lay blame--Charles contends with questions he's long been afraid to ask. Is his secret about Elizabeth his to share? And would his daughter want to know the truth, even if it could cost her everything she's ever known?"--